The Manchester Uveitis Clinic: The First 3000 Patients—Epidemiology and Casemix. (April 2015) - Jones, Nicholas P.
Abstract Purpose: To demonstrate the demography, anatomical, and diagnostic classification of patients with uveitis attending the Manchester Uveitis Clinic (MUC), a specialist uveitis clinic in the northwest of England, UK. Methods: Retrospective retrieval of data on a computerized database incorporating all new referrals to MUC from 1991 to 2013. Results: A total of 3000 new patients with uveitis were seen during a 22-year period. The anatomical types seen were anterior 46%; intermediate 11.1%; posterior 21.8%; and panuveitis 21.1%. The most common diagnoses were Fuchs heterochromic uveitis (11.5% of total), sarcoidosis-related uveitis (9.7%), idiopathic intermediate uveitis (7.9%), idiopathic acute anterior uveitis (7.0%), and toxoplasmosis (6.9%). Syphilis and tuberculosis-associated uveitis increased markedly in frequency during the study period. Conclusions: The uveitis casemix in this region reflects a predominantly white Caucasian population in a temperate country, but with changing characteristics owing to increasing immigration, enhanced diagnostic techniques, changes in referral pattern, and some real changes in disease incidence.